Targeted next-generation sequencing analysis in Italian patients with keratoconus - Lombardo, Marco; Camellin, Umberto; Gioia, Raffaella; Serrao, Sebastiano; Scorcia, Vincenzo; Roszkowska, Anna Maria; Lombardo, Giuseppe; Bertelli, Matteo; Medori, Maria Chiara; Alunni Fegatelli, Danilo; Vestri, Annarita; Mencucci, Rita; et al. (Eye (London), 2024)
Objective To report variants in 26 candidate genes and describe the clinical features of Italian patients with keratoconus (KC). Subjects/methods Sixty-four patients with a confirmed diagnosis of KC were enrolled in this genetic association study. Patients were classified into two study groups according to whether they had a confirmed diagnosis of progressive or stable KC. A purpose-developed Next Generation Sequencing (NGS) panel was used to identify and analyse the coding exons and flanking exon/intron boundaries of 26 genes known to be associated with KC and corneal dystrophies. Interpretation of the pathogenic significance of variants was performed using in silico predictive algorithms. Result The targeted NGS research identified a total of 167 allelic variants of 22 genes in the study population; twenty-four patients had stable keratoconus (n. 54 variants) and forty patients had progressive disease (n. 113 variants). We identified genetic variants of certain pathogenic significance in five patients with progressive KC; in addition, eight novel genetic variants were found in eight patients with progressive KC. Mutations of FLG, LOXHD1, ZNF469, and DOCK9 genes were twice more frequently identified in patients with progressive than stable disease. Filaggrin gene variants were found in 49 patients (76% of total), of whom 32 patients (80% of progressive KC group) had progressive disease. Conclusions Targeted NGS research provided new insights into the causative effect of candidate genes in the clinical phenotype of keratoconus. Filaggrin mutations were found to represent a genetic risk factor for development of progressive disease in Italy.